From the island’s point of view. Warfare and transformation in an Andean vertical archipelago - Tristan Platt (Journal de la Société des Américanistes)
From the island’s point of view. Warfare and transformation in an Andean vertical archipelago. The article combines John V. Murra’s theory of the « vertical archipelago » – a dynamic model of the changing historical relations between Andean societies, the complementary ecologies they inhabit, and emergent « State »-formations – with transformationalist theories developed among Amazonian peoples. Drawing on field-work with a longlived « archipelago » in the valleys of the Macha ayllu (Northern Potosí, Bolivia), the author shows the conflictive experience of valley « islands », which must invert their moiety affiliations to survive pressures from the larger groups in which they are implanted. The confusion of levels of segmentation and the « island » formation produces different valley alliances from those sought on the puna, while presupposing a shared horizon of ideas concerning violence. Andean warfare is characterized by the same « ontological instability » at the blurred frontier between humans and animals that is found among other Amerindian groups, and elsewhere in the world. Different kinds of shapeshifting during fiestas and warfare, and the reformulation of animal-human frontiers, are seen to be related to different social and historical contexts.